The effect of gender on the complications, pain intensity and pain management in hemodialysis patients - Atik, Derya; Karatepe, Hilal; Karatepe, Celalettin; Demir, Sultan; Çınar, Sezgi; Sökmen, Süleyman (International Journal of Research in Medical Sciences, 2016)
Background: Chronic renal failure (CRF) is a disease which threatens life, leads to significant loss of manpower and various complications, affecting almost every age group, mostly young adults. In the present study aim was to determine the effects to the complications, pain severity and pain management of gender differences in patients having HD treatment. Method: This study was a descriptive study. Data in research; patient information form, form questioning the way of pain management types, visual analog scale (VAS) were used. Results: Muscle cramps and nausea that show statistically significant differences between men and women, were more commonly seen in women (p≤0.05). HD applied CRF patients, they experienced musculoskeletal pain associated with most (36.9%) were determined to experience the more women than men (p<0.05). Perceived pain intensity was significantly higher in women (p<0.05). Conclusion: It was determined that patients had complications mostly muscle cramps, so their pain reasons are mostly related to musculoskeletal system and they had moderate pain, women had much more complications and pains related to musculoskeletal system.